Histone Deacetylase Inhibitors Restore the Odontogenic Differentiation Potential of Dental Pulp Stem Cells under Hyperglycemic Conditions - Hodjat, Mahshid; Farshad, Fatemeh; Gholami, Mahdi; Abdollahi, Mohammad; Saadat, Khandakar ASM (Current Stem Cell Research & Therapy, 2025)
ObjectiveComplications arising from diabetes can result in stem cell dysfunction, impairing their ability to undergo differentiation into various cellular lineages. The present study evaluated the effect of histone deacetylase inhibitors, Valproic acid and Trichostatin A, on the odontogenic differentiation potential of dental pulp stem cells under hyperglycemic conditions.MethodsStreptozotocin (STZ) induced diabetes mellitus in 12 male Wistar rats. Dental parameters were examined using micro-computed tomography. The odontogenic potential of human pulp stem cells exposed to 30 mM glucose was assessed through alkaline phosphatase assays, examination of gene expression for dentin matrix protein 1 and dentin sialoprotein using real-time PCR, and alizarin red staining for calcium deposition.ResultsAlong with reduced dentin thickness and root length in diabetic rats, the results revealed a significant increase in histone deacetylase 3 and 2 gene expressions in isolated diabetic pulp tissues compared to the control groups. The gene expression of odontogenic-related markers and alkaline phosphatase activity in human cultured pulp stem cells under hyperglycemic conditions significantly decreased. Adding Valproic acid and Trichostatin A restored the odontogenic differentiation markers, including calcium deposition, gene expression of dentin sialophosphoprotein, dentin matrix protein 1, and alkaline phosphatase activity.ConclusionThe data suggests that hyperglycemic conditions negatively impact the odontogenic potential of pulp mesenchymal stem cells. However, histone deacetylase inhibitors improve the impaired odontogenic differentiation capacity. This study implies that histone deacetylases may represent a potential therapeutic target for enhancing the regenerative mineralization of pulp cells in diabetic patients.
Keywords: Diabetes mellitus